Improved sealing ability promoted by calcium silicate-based root canal sealers - Tatiana Vieira de Melo; Marina Carvalho Prado; Raphael Hirata Junior; Sandra Rivera Fidel; Emmanuel João Nogueira Leal da Silva; Luciana Moura Sassone (Universidade Estadual de Campinas, 2018)
Aim: This study investigated the sealing ability produced by AH Plus (Dentsply DeTrey, Konstaz, Germany), EndoSequence BC sealer (Brasseler USA, Savannah, GA, USA), GuttaFlow (Coltène/Whaledent, Altstätten, France) and MTA Fillapex (Angelus, Londrina, Brazil). Methdos: A total of forty-six single-root human canines were prepared and randomly divided into four experimental groups (n=10): MTA Fillapex, EndoSequence BC Sealer, AH Plus or GuttaFlow. Teeth with intact crowns served as negative controls (n=3) and teeth filled with only gutta-percha served as positive controls (n=3). Teeth were mounted in a two-chamber apparatus and exposed to Enterococcus faecalis. The number of days over a 60-days period was recorded for the appearance of turbidity in the lower chamber. Kaplan-Meier method was used to estimate the survival curves. The nonparametric log-rank test was used to compare the survival curves using a significance level of 0.05. Results: The results at the end of the observation time were further analyzed by chi-square testing. All positive controls leaked within 24 h, whereas none of the negative controls leaked after 60 days. EndoSequence BC Sealer and MTA Fillapex had significant less bacterial leakage (P<0.05) than the other tested sealers. No significant difference between AH Plus and GuttaFlow was observed (P>0.05). Conclusion: In conclusion, calcium-silicate based root canal sealers promoted improved sealing ability when compared to other endodontic sealers.